Variations in Erythrocyte Count and Hemoglobin Levels in Blood Samples Collected Using Conventional Anticoagulants and Vacutainers with Different Secondary Homogenization Techniques - Batis, Afifah; Aliviameita, Andika (Universitas Nahdlatul Ulama Surabaya, 2025)
The choice of anticoagulants and the methods of homogenization are critical pre-analytical steps that can significantly influence the accuracy of laboratory results. This study aims to assess the differences in erythrocyte count and hemoglobin levels among blood samples processed with conventional anticoagulants and Vacutainer tubes, taking into account variations in secondary homogenization techniques. A laboratory experimental design was employed, utilizing 32 blood samples acquired from eight participants. The analysis was conducted using an automated hematology analyzer. Data were subjected to a Paired T-Test, indicating no significant differences in erythrocyte counts (p=0.617) and hemoglobin levels (p=0.510) between conventional EDTA samples that were homogenized four times and those homogenized eight times. However, a significant difference was noted in erythrocyte counts (p=0.018), while hemoglobin levels remained unaffected (p=0.393) in EDTA vacutainer samples subjected to four versus eight rounds of secondary homogenization. Additionally, a significant difference was found in both erythrocyte counts (p = 0.008) and hemoglobin levels (p < 0.0001) between conventional EDTA samples and those subjected to four rounds of secondary homogenization using vacutainers. Similarly, there was a significant difference in erythrocyte counts (p = 0.006) and hemoglobin levels (p = 0.014) between conventional EDTA samples and Vacutainer samples that underwent eight rounds of homogenization. Keywords: Blood Specimen Collection; EDTA; Erythrocyte; Hemoglobin; Secondary Homogenization